Regenerasi Kedelai melalui Kultur Epikotil dan Teknik Aklimatisasi - Slamet, Slamet; Pardal, Saptowo J.; Herman, M.; Wartono, Wartono (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2011)
Regeneration of induced callus growth into whole plants is an important step in genetic transformation. Soybean is a recalcitrant plant regeneration process which can not always be repeated often (irreproducible). Therefore, the standard soybean callus regeneration method is difficult to obtain. This research was conducted to obtain a suitable medium for the regeneration and acclimatization techniques for soybean plant. The regeneration experiment used soybean sprouts of Sindoro cultivar on five kinds of media, with MS and B5 basal media plus a few types and concentrations of growth regulators, arranged on completely randomized design with three replications. Each replication consisted of five explants per bottle. Observations were made on the number of explants forming shoots, number of shoots of each explant, number of roots, and shoots length. Results showed that the culture of epicotyl had a high regeneration rate (>90%), and B5 media was the most suitable for plant regeneration of callus derived from epicotyl explants of soybean. Acclimatization of plantlet derived from epicotyl and one putative transgenic (TO) plant resulted in 99% degree of success. Plantlets from epicotyl culture of soybean Sindoro cultivar and putative transgenic plants were successfully grown in the greenhouse and subsequently produced pods.